Kasık fıtığı onarımında kullanılan total ekstra peritoneal (TEP) onarım tekniğinde preperitoneal alanın disseksiyonunda balonlu ve balonsuz diseksiyon yöntemlerinin karşılaştırılması / Comparing baloon dissection and non baloon blunt dissection in TEP hernia repair technique - BİROL, Selim (My University, 2011)
BAKGROUND AND PURPOSE: Despite being costly use of dissection balon inTotal Ekstra Peritoneal (TEP) inguinal hernia operation is widely accepted and is believed to ease the operation. In this prospective randomized trial we aimed to define ,if any, the superiorities of balon dissection of preperitoneal space against non-baloon blunt endıcamera dissection.PATIENTS AND METHODS: Totally 40 patients, 20 of whom were randomized in Baloon Dissection group , and the rest in Camera Dissection grup undervent unilateral TEP inguinal hernia repair. Demographic data like age, sex, height, weight, BMI, distance between SIASs, and distance between pubic bne and umilicus were recorded. All the TEP operations were videorecorded from beginning to end. Early and late postoperative pain assessement were carried out through VAS. Intraoperative complications like bleeding,peritoneal laceration, conversion to open surgery, and objective surgical difficulty scale points were recorded.The timing of seeing the epigastric vessesls, pubic bone, peritoneal dissection time, peritonel reduction time and mesh placement time were recording according to the video records. Postoperative complications like hematoma,seroma,chronic groin pain,reccurence,infection and total postoperative control number were recorded. Lastly the total cost per patient between two groups was analysed.RESULT: No statistical difference was recorded between the parameters mentioned above but cost. Cost was statistically low in the Camera Dissection group (p<0,0001).CONCLUSION: Looking trough all the parametres mentioned before, it is understood that baloon dissection adds no benefit over Camera dissection except increasing the cost significantly. Morever Balon dissection did not add any extra peroperative or postoperative risk nor complication comparing to Baloon dissection. The objective surgical difficulty scale for tep points were also very close that enforces our thougt that both methods are identical excluding the hight cost of the dissection baloon. Considering all the results we advocate camera dissection comparing the baloon method.
Comparing baloon dissection and non baloon blunt dissection in TEP hernia repair technique
AMAÇ: TEP herni onarım tekniğinde kullanılan balonlu ve balonsuz preperitoneal diseksiyon yönteölerinin objektif kriterlerle karşılaştırılması ve birbiribirine iyilrşme, ağrı, nüks ve maliyet gibi parametreler açısından üstünlüğünün olup olmadığının gösterilmesi METOD: Toplam 40 hasta , 20'si balonlu 20' balonsuz (kamera diseksiyonu) yöntemle opere edilmiş olup preop perop ve postop datalar ve operasyon videokayıtlarından elde edilen parametreler randomize prospektif yöntemle karşılaştırıldı SONUÇ: Her iki yöntem teknik zorluk ve postop iyileşme,hasta konforu ve nüks gibi parametreler açısından birbirine denk olmakla beraber Balonsuz (Kamera) diseksiyonu yöntemi Balonlu yöntemden maliyet avantajı açısından istatistiksel olarak anlamlı derecede üstündür
Keywords: Research Subject Categories::MEDICINE; Genel Cerrahi